PEREMPUAN DALAM KEPEMIMPINAN POLITIK DI INDONESIA - Baharudin, Baharudin (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2022)
This study aims to examine the roles, challenges, and contributions of women in political leadership in Indonesia. Through a qualitative approach with a literature review method, this study analyzes various relevant literature sources, including scientific journals, books, articles, and research reports. The results of the study show that despite increased awareness of the importance of women's involvement in politics, various social and structural barriers still hinder their participation. The implementation of the women's quota policy is often inconsistent, and support from political parties is still inadequate. In addition, social norms and gender stereotypes continue to be a significant challenge. However, women who succeed in political leadership positions bring positive changes in public policies that are more inclusive and gender-sensitive. This study recommends the need for greater and coordinated efforts to address these barriers and increase women's participation in politics in Indonesia.